2008
DOI: 10.1016/j.molcel.2008.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Multimegabase Silencing in Nucleolar Dominance Involves siRNA-Directed DNA Methylation and Specific Methylcytosine-Binding Proteins

Abstract: In genetic hybrids, the silencing of nucleolar rRNA genes inherited from one progenitor is the epigenetic phenomenon known as nucleolar dominance. An RNAi knockdown screen identified the Arabidopsis de novo cytosine methyltransferase, DRM2 and the methylcytosine binding domain proteins, MBD6 and MBD10 as activities required for nucleolar dominance. MBD10 localizes throughout the nucleus, but MBD6 preferentially associates with silenced rRNA genes, and does so in a DRM2-dependent manner. DRM2 methylation is tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
128
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(139 citation statements)
references
References 56 publications
8
128
1
2
Order By: Relevance
“…An RNAi approach has been used with Arabidopsis suecica, a hybrid of Arabidopsis and Arabidopsis arenosa, to determine factors involved in nucleolar dominance. This has shown the involvement of the histone deacetylases Histone Deacetylase1 and Histone Deacetylase6, the de novo DNA methyltransferase Domains Rearranged Methyltransferase2 (DRM2), and the methylcytosine binding domain proteins Methyl CpG Binding Domain6 (MBD6) and MBD10 (Preuss et al, 2008). Further confirmation that nucleolar dominance in plants involves RNA-directed DNA methylation was obtained by knockdown of RNA Dependent RNA Polymerase2, Dicer-like3, and DRM2, which disrupted the silencing of the Arabidopsisderived rRNA genes in A. suecica (Preuss et al, 2008).…”
Section: Nucleolar Chromatin and Epigeneticsmentioning
confidence: 89%
“…An RNAi approach has been used with Arabidopsis suecica, a hybrid of Arabidopsis and Arabidopsis arenosa, to determine factors involved in nucleolar dominance. This has shown the involvement of the histone deacetylases Histone Deacetylase1 and Histone Deacetylase6, the de novo DNA methyltransferase Domains Rearranged Methyltransferase2 (DRM2), and the methylcytosine binding domain proteins Methyl CpG Binding Domain6 (MBD6) and MBD10 (Preuss et al, 2008). Further confirmation that nucleolar dominance in plants involves RNA-directed DNA methylation was obtained by knockdown of RNA Dependent RNA Polymerase2, Dicer-like3, and DRM2, which disrupted the silencing of the Arabidopsisderived rRNA genes in A. suecica (Preuss et al, 2008).…”
Section: Nucleolar Chromatin and Epigeneticsmentioning
confidence: 89%
“…Specialized chromatin modification complexes that target rDNA genes have been described in budding yeast (Straight et al 1999), Arabidopsis Earley et al 2006;Preuss et al 2008), and in mammals (Murayama et al 2008). In Arabidopsis and mammals, these complexes reduce overall histone acetylation and direct histone methylation at lysine-9 of the histone H3 (H3K9me), leading to silencing of rDNA genes.…”
Section: Discussionmentioning
confidence: 99%
“…One early hypothesis was that specific rRNA genes are selectively activated, based on transcription factor binding affinities (6). However, subsequent studies in plants and mammals revealed that specific rRNA genes are selectively silenced via changes in cytosine methylation and repressive histone modifications (7)(8)(9)(10)(11)(12)(13). Subtle sequence differences among rRNA genes have been proposed to influence nucleosome positioning, or base-pairing with noncoding RNAs, thereby inhibiting or enabling regulatory proteins that influence cytosine methylation and/or histone modification (11,(14)(15)(16).…”
mentioning
confidence: 99%